KONTRIBUSI KOMODITAS KOPI TERHADAP PEREKONOMIAN WILAYAH KABUPATEN JEMBER - Novi Haryati (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2008)
This research aimed to understand: (1) coffee production regions in Jember regency are production base region; (2) spreading characteristic of coffee commodity in Jember regency directs to localization and specialization pricipallity; (3) coffee commodity sector contribution if it is compared with others sectors in supporting the developing of Jember regency economics; and (4) the multiplier impact given by coffee commodity sector and the linkages with other sectors in supporting Jember regency economics. This research uses secondary data from year 2001 until year 2005. The method of analyze data used are Location Quotient Analysis, Localization and Specialization Analysis, and also Input Output Analysis. The result  shows that: (1) regions  that be coffee production base sub districts are Patrang, Ledokombo, Sumberjambe, Jelbuk, Silo, Panti, and Sukorambi because these sub districts shows Location Quotient value that is more than one. It means that the sub districts can fulfill the need of coffee commodity production and also  export tendency to other sub districts; (2) the characteristic of coffee production that is spreaded in Jember Regency does not direct to localisazation and specialization principality; (3) coffee commodity sector contribution if it is compared with other sectors in supporting the developing of Jember regency economic is low (4) coffee commodity sector gives high simple output multiplier impact as much as 1, 02, but it gives low total output multiplier impact as much as 0,67. The value of coffee commodity income multiplier impact is high. Key words : contribution sector to GDP